2015
DOI: 10.1016/j.cub.2015.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Insight Reconfigures Hippocampal-Prefrontal Memories

Abstract: Our memories are remarkably dynamic and allow us to reinterpret the past once new information comes to light. Gaining novel insights can lead to mental reorganization of previously unrelated events, thus linking them into narratives. The hippocampus and medial prefrontal cortex (mPFC) support integration of partially overlapping events, but the neural mechanisms underlying the reorganization of memories for the formation of coherent narratives remain elusive. Here, we combine fMRI with The Sims 3 videos of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(151 citation statements)
references
References 44 publications
11
128
2
1
Order By: Relevance
“…Consistent with these findings on rodents, several fMRI studies have shown that the hippocampus is engaged as related memories are assimilated and integrated to support novel transitive inferences in humans (Heckers et al, 2004; Preston et al, 2004; Zalesak & Heckers, 2009; Kumaran et al, 2009; Zeithmova & Preston, 2010, 2012; Milivojevic et al, 2015). Notably, these roles in organizing memories extend to a range of non-spatial tasks including learning a hierarchical organization (Piaget’s transitive inference task) and associative organizations (the associative inference task and acquired equivalence; Shohamy & Wagner, 2008; Wimmer & Shohamy, 2012; see Zeithamova et al, 2012; Milivojevic et al, 2015). …”
Section: What Is the “Memory Code” In The Hippocampus?mentioning
confidence: 63%
“…Consistent with these findings on rodents, several fMRI studies have shown that the hippocampus is engaged as related memories are assimilated and integrated to support novel transitive inferences in humans (Heckers et al, 2004; Preston et al, 2004; Zalesak & Heckers, 2009; Kumaran et al, 2009; Zeithmova & Preston, 2010, 2012; Milivojevic et al, 2015). Notably, these roles in organizing memories extend to a range of non-spatial tasks including learning a hierarchical organization (Piaget’s transitive inference task) and associative organizations (the associative inference task and acquired equivalence; Shohamy & Wagner, 2008; Wimmer & Shohamy, 2012; see Zeithamova et al, 2012; Milivojevic et al, 2015). …”
Section: What Is the “Memory Code” In The Hippocampus?mentioning
confidence: 63%
“…Even though this appears unlikely due to the sampling of each direction from multiple locations (Figure 1—figure supplement 2) we compared the visual similarity of the scenes to be imagined based on a set of visual features (Milivojevic et al, 2015). For each trial, the view from the start position facing the direction of the target building was captured at a resolution of 1024 × 768 pixels.…”
Section: Methodsmentioning
confidence: 99%
“…The paired associate inference (PAI) task [91,[96][97][98] provides an example of a task that involves the hippocampus and captures the essence of requiring cross-item inferences required in other relevant tasks (such as the transitive inference task reviewed in [4]). In the study phase of the PAI task, subjects view pairs of objects (e.g., AB, BC) that are derived from triplets (i.e., ABC) or larger object sets (e.g., sextets: A, B, C, D, E, F; Box 6).…”
Section: Cross-item Inferencesmentioning
confidence: 99%
“…In the crucial test trials, subjects are tested on their ability to appreciate the indirect relationships between items that were never presented together (e.g., A and F in the sextet version). Evidence for a role of the hippocampus in supporting inference in such settings [91,92,[96][97][98] naturally raises the question of the neural mechanisms underlying this function, and has been seen as challenging the view that the hippocampus only stores separate representations of specific items or experiences. Indeed, the findings have been taken as supporting 'encoding-based overlap' models [4,95,99,100], in which it is proposed that the hippocampus supports inference by using representations that integrate or combine overlapping pairs of items (e.g., AB and BC in the triplet version of the PAI task).…”
Section: Cross-item Inferencesmentioning
confidence: 99%